Depth relationships and measures of tissue thickness in dorsal midbrain. Issue 18 (1st September 2020) - Truong, Paulina; Kim, Jung Hwan; Savjani, Ricky; Sitek, Kevin R.; Hagberg, Gisela E.; Scheffler, Klaus; Ress, David
Abstract: Dorsal human midbrain contains two nuclei with clear laminar organization, the superior and inferior colliculi. These nuclei extend in depth between the superficial dorsal surface of midbrain and a deep midbrain nucleus, the periaqueductal gray matter (PAG). The PAG, in turn, surrounds the cerebral aqueduct (CA). This study examined the use of two depth metrics to characterize depth and thickness relationships within dorsal midbrain using the superficial surface of midbrain and CA as references. The first utilized nearest‐neighbor Euclidean distance from one reference surface, while the second used a level‐set approach that combines signed distances from both reference surfaces. Both depth methods provided similar functional depth profiles generated by saccadic eye movements in a functional MRI task, confirming their efficacy for delineating depth for superficial functional activity. Next, the boundaries of the PAG were estimated using Euclidean distance together with elliptical fitting, indicating that the PAG can be readily characterized by a smooth surface surrounding PAG. Finally, we used the level‐set approach to measure tissue depth between the superficial surface and the PAG, thus characterizing the variable thickness of the colliculi. Overall, this study demonstrates depth‐mapping schemes for human midbrain that enables accurate segmentation of the PAG and consistent depth and thickness estimates of the superior and inferior colliculi. Abstract : This study examined the use of two depth metrics to characterize depth and thickness relationships within dorsal midbrain using the superficial surface of midbrain and the cerebral aqueduct as references. The first used nearest‐neighbor Euclidean distance from one reference surface, while the second used a level‐set approach that combines signed distance from both reference surfaces. Both methods are useful for particular applications, but the level‐set approach should be particularly useful to characterize functional activity deep in the midbrain.